ORGANIZATIONAL CLIMATE AND ITS INFLUENCE ON THE STRUCTURE OF THE STRATEGIC PLAN FOR HIGHER EDUCATIONAL INSTITUTE PRIVATE PAULO FREIRE LOCATED IN THE DISTRICT OF COMAS - Huamán Mejía, María Celina (2014)
The results of research on the influence of organizational climate in the structuring of the Strategic Plan in the Higher Pedagogical Institute Paulo Freire Private presented in this article. The analysis of this organization allows establishing the relationship of organizational climate, with respect to the satisfaction of the stakeholders of the institution according to the dimensions of Litwin and Stringer; and the Strategic Plan, to improve their processes in order to become an accredited and recognized institution in the country.